KDYProvider preferences for delivery of HIV care coordination services: results from a discrete choice experiment. Issue 3 (24th March 2022) - Zimba, Rebecca; Fong, Chunki; Conte, Madellena; Baim‐Lance, Abigail; Robertson, McKaylee; Carmona, Jennifer; Gambone, Gina; Nash, Denis; Irvine, Mary
Abstract: Introduction: The PROMISE study was launched in 2018 to assess and document the implementation of changes to an existing HIV Care Coordination Programme (CCP) designed to address persistent disparities in care and treatment engagement among persons with HIV in New York City. We evaluated provider endorsement of features of the CCP to understand drivers of engagement with the programme. Methods: We used a discrete choice experiment to measure provider endorsement of four CCP attributes, including: (1) how CCP helps with medication adherence, (2) how CCP helps with primary care appointments, (3) how CCP helps with issues other than primary care and (4) where CCP visits take place (visit location). Each attribute had three to four levels. Our primary outcomes were relative importance and part‐worth utilities, measures of preference for the levels of the four CCP program attributes, estimated using a hierarchical‐Bayesian multinomial logit model. All non‐medical providers in the core CCP positions of patient navigator, care coordinator and programme director or other administrator from each of the 25 revised CCP‐implementing agencies were eligible to participate. Results: We received responses from 152 providers, 68% of whom identified as women, 49% identified as Latino/a, 34% identified as Black and 60% were 30–49 years old. Visit location (28.6%, 95% confidence interval [CI] 27.0–30.3%) had the highest relative importance, followed by how staff help with ART adherence (24.3%, 95% CI 22.4–26.1%), how staff help with issues other than primary care (24.2%, 95% CI 22.7–25.7%) and how staff help with primary care appointments (22.9%, 95% CI 21.7–24.1%). Within each of the above attributes, respectively, the levels with the highest part‐worth utilities were home visits 60 minutes from the program or agency (utility 19.9, 95% CI 10.7–29.0), directly observed therapy (utility 26.1, 95% CI 19.1–33.1), help with non‐HIV specialty medical care (utility 26.5, 95% CI 21.5–31.6) and reminding clients about and accompanying them to primary care appointments (utility 20.8, 95% CI 15.6–26.0). Conclusions: Ongoing CCP refinements should account for how best to support and evaluate the intensive CCP components endorsed by providers in this study.